Volume 9: Transportation Systems; Safety Engineering, Risk Analysis and Reliability Methods; Applied Stochastic Optimization, U 2011
DOI: 10.1115/imece2011-63715
|View full text |Cite
|
Sign up to set email alerts
|

Model Based Study of Stability Limits for Three Wheeled Vehicles Using ADAMS/Car

Abstract: Three-wheeled motor vehicles have been around for close to a half a century now, but they have largely remained in the realm of recreational or concept vehicles. Due to increasing fuel prices and an emphasis on fuel efficient design, the automotive industry is exploring the three-wheeled option now more than ever as a mainstream daily-use vehicle. The trend is evident from the Automotive X-Prize which featured six teams with three-wheeled vehicle designs to meet the fuel efficiency target [1]. A three-wheeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…e axle load of the vehicle is generally seen as a key factor related to the vehicle's dynamic performance [36]. For the articulated vehicles, most of them operate in the engineering area.…”
Section: Influence Of the Payload Variationmentioning
confidence: 99%
“…e axle load of the vehicle is generally seen as a key factor related to the vehicle's dynamic performance [36]. For the articulated vehicles, most of them operate in the engineering area.…”
Section: Influence Of the Payload Variationmentioning
confidence: 99%
“…The collected data showed that the driver was preparing to apply brake when the vehicle takes a turn. Rao et al 9 Three-wheeled conventional vehicle…”
Section: Not Applicablementioning
confidence: 99%